Coordinated expression of p300 and HDAC3 upregulates histone acetylation during dentinogenesis. Issue 3 (6th November 2019) - Tao, Huangheng; Li, Qiuhui; Lin, Yuxiu; Zuo, Huanyan; Cui, Yu; Chen, Shuo; Chen, Zhi; Liu, Huan
Abstract: Cellular differentiation is caused by highly controlled modifications in the gene expression but rarely involves a change in the DNA sequence itself. Histone acetylation is a major epigenetic factor that adds an acetyl group to histone proteins, thus altering their interaction with DNA and nuclear proteins. Illumination of the histone acetylation during dentinogenesis is important for odontoblast differentiation and dentinogenesis. In the current study, we aimed to discover the roles and regulation of acetylation at histone 3 lysine 9 (H3K9ac) and H3K27ac during dentinogenesis. We first found that both of these modifications were enhanced during odontoblast differentiation and dentinogenesis. These modifications are dynamically catalyzed by histone acetyltransferases (HATs) and deacetylases (HDACs), among which HDAC3 was decreased while p300 increased during odontoblast differentiation. Moreover, overexpression of HDAC3 or knockdown p300 inhibited odontoblast differentiation in vitro, and inhibition of HDAC3 and p300 with trichostatin A or C646 regulated odontoblast differentiation. Taken together, the results of our present study suggest that histone acetylation is involved in dentinogenesis and coordinated expression of p300‐ and HDAC3‐regulated odontoblast differentiation through upregulating histone acetylation. Abstract : In conclusion, this study illustrated the expression pattern of H3K9ac and H3K27ac during dentinogenesis and odontoblast differentiation. We then found that histone acetylases P300 and HDAC3 showed unique expression patterns during differentiation. We also confirmed that histone acetylases P300 and HDAC3 could regulate odontoblast differentiation themselves through modulating histone acetylation.